Antecedents of safety behaviour among healthcare workers in Hospital Pakar Sultanah Fatimah, Muar, Johor - Mohd Aidil, Musa (2020)
Safety behavior impacts the actions that can be taken to address safety and health issues at the workplace. The purpose of this study was to determine the relationship between nature of job, management style, coworkers' influence, and the level of injury severity which may affect the safety behavior among healthcare workers at Sultanah Fatimah Muar Specialist Hospital. The study was conducted a quantitative method in which data and information were obtained through distributing the questionnaire to 400 respondents among the healthcare workers and 307 respondents gave their feedback which came from various clinical staff positions at the Sultanah Fatimah Muar Johor Specialist Hospital. Data were collected and analyzed using SPSS (Statistical Package for Social Science) software version 25. The results of the study showed significant correlations between all of the independent variables; nature of job, management style, coworkers’ influence, and level of injury severity of the healthcare staff toward the dependent variable of safety behavior in the scenario of reporting violence at Sultanah Fatimah Muar Specialist Hospital. Based on the findings of the study, it is recommended that organizations within the Ministry of Health Malaysia (MoH) should work hard to raise awareness among healthcare staff and strengthen training on violence to address workplace safety issues.